VD_FINDINFO HC / 2015 / 613 vom 16. Juli 2015 - VD Tribunal cantonal (2015)
PROCÉDURE DE CONCILIATION, TRANSACTION JUDICIAIRE, MESURE PROVISIONNELLE | 105 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH)